ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS V SEKOLAH DASAR SE-GUGUS 7 KECAMATAN TAMPAN KOTA PEKANBARU - Juwita, Atika; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : One of the factors that influence the student's IPS learning process is motivation. The purpose of this study to determine what factors that affect student learning motivation on learning IPS class V Se-Cluster 7 Tampan Disctrict Pekanbaru City and to determine which factors affect the greatest motivation of student learning on learning IPS class V Se-cluster 7 Tampan Disctrict Pekanbaru City. This research uses descriptive quantitative method. Sampling technique using Simple Random Sampling technique. Data collection techniques using questionnaires. Data analysis technique used is descriptive analysis technique. The result showed that the factors that influence student's learning motivation on IPS learning are 17,9% influenced by student aspiration/aspiration, 17,5% influenced by dynamic elements, 16,9% influenced by student's behavior, 16 , 3% influenced by teacher's effort in to learn student, 16,1% influenced by condition of student environment, 15,3% influenced by ability of student. So the bigger factor influence student's learning motivation on learning IPS class V Elementary School of Class of 7 Tampan Disctrict Pekanbaru City that is internal factor aspiration/aspiration of student that influence equal to 17,9%.Keyword : Motivation in Social Studies